APPLICATION OF THE 4S PERSONAL APPROACH CONCEPT WITH OUTPATIENT SATISFACTION AT PRIVATE MIDWIFERY PRACTICES - Rika Mursyida, Mursyida; Siska Desta Roza (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2026)
Patients' expectations of receiving the best service pose a challenge for healthcare providers, especially independent midwifery practices, to continuously improve service quality and care for outpatient patients. The quality of midwifery services is one of the indicators of service success. The provision of midwifery care is also based on the attitude of the 4S personal approach concept (greet, say hello, smile, be polite) to enhance the care for patient satisfaction. Patient satisfaction will be fulfilled if the quality of service provided meets the expectations of outpatient patients in independent midwifery practices. The purpose of this study is to analyze the relationship between the application of the 4S personal approach concept and outpatient patient satisfaction. The non-parametric study design is of the Spearman’s rho analysis type, with bivariate analysis test results showing a P value of 0.001 < 0.005, thus Ha is accepted. The participants are outpatients at PMB, totaling 124 individuals from August to December 2025, with the instrument being a questionnaire consisting of 36 Likert scale questions. The results of the univariate analysis showed that the 4S personal approach concept was categorized as positive by 79 people (63.7%) and negative by 45 people (36.2%), with a total sample size of 124 patients. The domain of outpatient satisfaction was categorized as very satisfied by 58 people (46.7%), satisfied by 53 people (42.7%), dissatisfied by 11 people (8.8%), and very dissatisfied by 2 people (1.6%). The results of this study indicate a relationship between the application of the 4S personal approach concept and outpatient satisfaction at the Independent Midwife Practice. In conclusion, the 4S personal approach is an important factor in building comfort and trust in communication aspects, and the midwife's behavior plays a crucial role in shaping patients' positive perceptions of service satisfaction.